Projected distribution patterns of Alpinia officinarum in China under future climate scenarios: insights from optimized Maxent and Biomod2 models - Kang, Yong; Lin, Fei; Yin, Junmei; Han, Yongjie; Zhu, Min; Guo, Yuhua; Tang, Fenling; Li, Yamei (Frontiers in Plant Science, 2025)
Alpinia officinarum, commonly known as Galangal, is not only widely used as a medicinal plant but also holds significant ornamental value in horticulture and landscape design due to its unique plant structure and floral aesthetics in China. This study evaluates the impact of current and future climate change scenarios (ssp126, ssp245, ssp370, and ssp585) on the suitable habitats for A. officinarum in China. A total of 73 reliable distribution points for A. officinarum were collected, and 11 key environmental variables were selected. The ENMeval package was used to optimize the Maxent model, and the potential suitable areas for A. officinarum were predicted in combination with Biomod2. The results show that the optimized Maxent model accurately predicted the potential distribution of A. officinarum in China. Under low emission scenarios (ssp126 and ssp245), the suitable habitat area increased and expanded towards higher latitudes. However, under high emission scenarios (ssp370 and ssp585), the suitable habitat area significantly decreased, with the species distribution range shrinking by approximately 3.7% and 19.8%, respectively. Through Multivariate environmental similarity surface (MESS) and most dissimilar variable (MoD) analyses revealed that increased climate variability under high emission scenarios, especially in ssp585, led to large-scale habitat contraction due to rising temperatures and unstable precipitation patterns. Changes in the center of suitability location showed that the current center of A. officinarum’s suitable habitat is located in Guangxi, China. Under low emission scenarios, the center of suitability gradually shifts northwest, while under high emission scenarios, this shift becomes more pronounced. These findings provide a scientific basis for the conservation of A. officinarum germplasm resources and the management strategies in response to climate change.